Workshop Manajemen dan Substansi Pengelolaan Jurnal Ilmiah Menuju Jurnal Terakreditasi Nasional dan Internasional - Muhamad Syazali; Hayatul Khairul Rahmat; I Dewa Ketut Kerta Widana; Ence Darmo Jaya Supena; Rahmat Basuki; Miftahul Huda Fendiyanto; Adhi Kusumadjati; Mo Awwanah (Indonesian Journal of Emerging Trends in Community Empowerment, 2023)
Workshop on the management and substance of managing scientific journals towards national and international accredited journals aim to gain an understanding of how the management and substance of management of scientific journals towards national and international accredited journals within the Faculty of Military Mathematics and Natural Sciences, the Republic of Indonesia Defense University. The procedure for implementing activities starts from the preparation, implementation, and closing stages. This activity is very useful for improving the quality of scientific journal management at the Faculty of Military Mathematics and Natural Sciences, the Republic of Indonesia Defense University towards national and international accredited journals. This can also be seen from the response and enthusiasm of the participants who asked when carrying out management workshop activities and the substance of managing scientific journals towards this national and international accredited journal.